Education for Young Women about Vulva Hygiene Behavior During Menstruation at 3 Middle Schools in Cilincing District, North Jakarta - Nurlelawati, Ella; Supriyono, Ragil; Siswosuharjo, Partono (Akademi Keperawatan RSPAD Gatot Soebroto, 2022)
The community considers that reproductive health is still taboo to be discussed by teenagers, in Jakarta there are still many children who have low knowledge. This study aims to determine the relationship to vulva hygiene behavior in adolescents during menstruation in young women. This study used a cross-sectional design with a total of 275 female students who had experienced menstruation using a stratified random sampling technique. Results Data analysis used univariate, bivariate analysis using the chi square test and multivariate with multiple logistic regression tests to determine the dominant factor associated with vulva hygiene behavior during menstruation. The results showed that female adolescents performed vulva hygiene incorrectly as much as 62.%, and the dominant variable on vulva hygiene behavior in female adolescents during menstruation was attitudes towards vulva hygiene with an OR = 2,820 meaning that female adolescents with a positive attitude were 3 times more likely to perform vulva hygiene in comparison with young women who have a negative attitude. After being controlled by the variable exposed to media information about vulva hygiene. Efforts to further improve the attitude of adolescents towards vulva hygiene behavior during menstruation through increased knowledge about proper reproductive health. By inviting health practitioners from the local health center in order to increase knowledge and provide awareness of the students in terms of vulva hygiene behavior.